Pengaruh Struktur Kepemilikan terhadap Biaya Ekuitas dengan Manajemen Laba Sebagai Variabel Mediasi - Lorenza, Linda; Wibowo, Raden Arief (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This study aims to analyze the effect of ownership structure, proxied by family ownership, institutional ownership, and foreign ownership, on equity costs, with earnings management as a mediating variable. Manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021 were the population in this study, totaling 37 companies each year (233 units of analysis). Data analysis was conducted using mediation regression with path analysis using Eviews software. The results of this study show that direct testing in path analysis indicates that family ownership, institutional ownership, and foreign ownership on profit management are acceptable. However, in the indirect test of the influence of ownership structure on equity costs through earnings management, the results were rejected, meaning that earnings management cannot be considered a mediating variable because the results of the Sobel test did not meet the criteria. If the Sobel test coefficient value is greater than the t-table value, it can meet the mediation criteria.